Astroglial modulation of transient potassium current development in cultured mouse hippocampal neurons - Wu, RL (J Neurosci, 1994)
Hippocampal neurons exhibit three voltage-gated potassium currents, two transient currents and a delayed rectifier, that influence numerous aspects of electrogenesis including action potential duration and accommodation to sustained depolarization. These currents, termed A-, D- , and K-currents, respectively, can be distinguished based on kinetics, steady state inactivation characteristics, and sensitivity to 4- aminopyridine (see Wu and Barish, 1992b). We have compared the voltage- gated potassium currents in voltage-clamped pyramidally shaped cultured hippocampal neurons growing on or touching glial fibrillary acidic protein-expressing astroglia (termed on-glia or touching-glia neurons, respectively) with those in similar neurons growing directly on a coated glass substrate (termed off-glia neurons). We observed differences in the wave forms of total potassium current that correlated with the extent of astroglial contact. After 5–7 d in culture, A-current amplitude in off-glial neurons was approximately 19% of that of neurons growing in the normal (for culture) on-glia configuration. D-current amplitude tended to be larger in these off- glia neurons. Neurons in contact with astroglia had greater membrane area than off-glia neurons. Comparison of current densities (current at a fixed voltage normalized to capacitance and expressed in units of pA/pF) indicated that A-currents were the major component of transient potassium current in on- and touching-glia neurons, while D-currents were more dominant in off-glia neurons. Astroglia influenced membrane currents by a surface- or extracellular matrix-associated mechanism, rather than by free diffusion of a soluble factor, as differences were observed between closely adjacent neurons on the same coverslip. Living glia were required, as potassium currents in neurons grown on dried or methanol-fixed glia resembled those of off-glia neurons. On-glia neurons in cultures treated with an RNA synthesis inhibitor [DRB (5,6- dichloro-1-beta-D-ribofuranosylbenzimidazole)] for 5–7 d had reduced whole-cell capacitance and A-current amplitude. This effect was localized to DRB actions on underlying astroglia, not on the neurons. Action potentials elicited by current injection varied with astroglial contact. In on-glia neurons with relatively larger A-currents a delay was seen in the onset of firing after depolarization. In contrast, action potentials in off-glia neurons rose smoothly after initiation of depolarization. We conclude that astrocytes modulate the appearance of transient potassium currents in hippocampal pyramidal neurons by inducing development of A-current.(ABSTRACT TRUNCATED AT 400 WORDS)